Combined balance and plyometric training enhances knee function, but not proprioception of elite male badminton players: A pilot randomized controlled study - Zhou, Limingfei; Gong, Wangcheng; Wang, Shixian; Guo, Zhenxiang; Liu, Meng; Chuang, Samuel; Bao, Dapeng; Zhou, Junhong (Frontiers in Psychology, 2022)
Objectives To investigate the effect of combined balance and plyometric training on knee function and proprioception of elite badminton athletes. Methods Sixteen elite male badminton players (age: 20.5 ± 1.1 years, height: 177.8 ± 5.1 cm, weight: 68.1 ± 7.2 kg, and training experience: 11.4 ± 1.4 years) volunteered to participate and were randomly assigned to a combined balance and plyometric training (CT) (n = 8) and plyometric (PT) group (n = 8). The CT group performed balance combined with plyometric training three times a week over 6 weeks (40 min of plyometrics and 20 min of balance training); while the PT group undertook only plyometric training for the same period (3–4 sets × 8–12 reps for each exercise). Both groups had the same technical training of badminton. Results The knee function and proprioception were assessed at baseline and after the intervention by measuring the performance of single-legged hop tests (LSIO, LSIT, LSIC, LSIS), standing postural sway (COPAP, COPML), and LSI of dominant leg and non-dominant leg. The results showed that as compared to PT, CT induced significantly greater improvements in LSIT and LSIS (p < 0.001) and significant greater percent increase in NAP (p = 0.011). The changes in LSIO, LSIC, DAP, NAP, LSIAP, DML, NML, and LSIML induced by CT did not differ from that induced by PT (p > 0.213). Conclusion In elite badminton players, intervention using CT holds great promise to augment the benefits for knee function compared to the intervention using PT only, and at the same time, with at least comparable benefits for proprioception. Future studies are needed to examine and confirm the results of this study.